Effect of selenium on physiological responses in black gram and rice seedlings under cadmium and lead stress: A comparative study: Selenium mitigation of Cd and Pb stress - Samal, Nibedita; Das, Manoja; Behera, Kambaska Kumar; Sarangi, Ansul (ORYZA-An International Journal of Rice, 2025)
The present study evaluates the physiological, biochemical, and antioxidative responses of (Vigna mungo (L.) Hepper, cv. Ujala) and rice (Oryza sativa L.cv. Arnapurna) seedlings under cadmium (Cd) and lead (Pb) stress, and examines the ameliorative potential of selenium (Se) supplementation (10 mg L-¹). Cd and Pb exposure significantly inhibited growth and biomass in a dose-dependent manner. In black gram, shoot and root length decreased by up to 27.27% and 25.01% under Cd stress (T3), and by 31.82% and 35.70% under Pb stress (T6), respectively. Similarly, shoot and root biomass declined by 23.30% and 49.28% (Cd), and by 22.15% and 53.62% (Pb). Rice exhibited shoot length reductions of 19.64% and root length reductions of 23.3% under Cd stress. Photosynthetic pigments were also reduced, with chlorophyll-a, total chlorophyll, and carotenoids decreasing by up to 29.22%, 24.27%, and 21.3% in black gram, and 29.2%, 27.15%, and 33.3% in rice, respectively. Biochemically, Cd and Pb caused declines in protein (up to 17.65%), sugar (up to 25.64%), and sharp increases in proline levels up to 925.0% in black gram and 760.0% in rice. Antioxidant enzyme activities (POX, CAT, SOD) increased 2.4-3.1fold under stress, indicating elevated oxidative damage. Selenium supplementation significantly alleviated these effects. In Cd-stressed black gram, Se increased shoot and root lengths by 22.7% and 28.6%, and in rice by 10.7% and 20.0%, respectively, compared to controls. Pigment content recovered markedly, with chlorophyll-a increasing by 75.9% (black gram) and 50.8% (rice) over Cd-only treatments. Protein and sugar content also improved (up to 36.84% and 41.54%), while proline remained elevated, further increasing by up to 153.3%. Antioxidant enzymes were further enhanced by Se, with POX, CAT, and SOD activities increasing by 3.5-, 3.3-, and 2.7-fold in rice shoots, and similar trends observed in roots. The findings confirm that selenium plays a crucial role in mitigating Cd and Pb toxicity by enhancing growth, stabilizing cellular metabolism, and strengthening antioxidant defenses in both crops.